Protein palmitoylation is involved in regulating mouse sperm motility via the signals of calcium, protein tyrosine phosphorylation and reactive oxygen species - Yuping Xiong; Chenchen Yi; Haixia Zheng; Ya Ni; Yamei Xue; Kun Li (Biological Research)
Abstract Background Protein palmitoylation, a critical posttranslational modification, plays an indispensable role in various cellular processes, including the regulation of protein stability, mediation of membrane fusion, facilitation of intracellular protein trafficking, and participation in cellular signaling pathways. It is also implicated in the pathogenesis of diseases, such as cancer, neurological disorders, inflammation, metabolic disorders, infections, and neurodegenerative diseases. However, its regulatory effects on sperm physiology, particularly motility, remain unclear. This study aimed to elucidate the mechanism by which protein palmitoylation governs sperm motility. Methods Protein palmitoylation in situ in mouse sperm was observed using innovative click chemistry. Sperm motility and motion parameters were evaluated using a computer-assisted sperm analyzer (CASA) after treatment with 2-bromopalmitic acid (2BP), a specific inhibitor of protein palmitoylation. Protein palmitoylation levels were confirmed by the acyl-biotin exchange (ABE) method. The interplay between protein palmitoylation, protein tyrosine phosphorylation, and intracellular calcium was investigated using Western blotting, ABE method, and fluorescent probes. The regulation of reactive oxygen species was also examined using fluorescent probes. Results Localized patterns and dynamics of protein palmitoylation in distinct sperm regions were revealed, including the midpiece, post-acrosomal region, acrosome, and head. Alterations in protein palmitoylation in sperm were observed under in vitro physiological conditions. Treatment with 2BP significantly affected sperm motility and motion parameters. The study revealed interactions between protein palmitoylation, including heat shock protein 90, and protein kinase A/protein kinase C-associated protein tyrosine phosphorylation and intracellular calcium. Additionally, protein palmitoylation was found to be involved in reactive oxygen species regulation. Conclusions Protein palmitoylation regulates sperm motility through calcium signaling, protein tyrosine phosphorylation, and reactive oxygen species. This study revealed the characteristics of protein palmitoylation in sperm and its role in regulating sperm motility, thereby providing novel insights into the causes of asthenozoospermia associated with sperm motility in humans.